2003
DOI: 10.1182/blood-2003-01-0283
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic mice overexpressing erythropoietin adapt to excessive erythrocytosis by regulating blood viscosity

Abstract: Severe elevation of red blood cell number is often associated with hypertension and thromboembolism resulting in severe cardiovascular complications. However, some individuals such as high altitude dwellers cope well with an increased hematocrit level. We analyzed adaptive mechanisms to excessive erythrocytosis in our transgenic (tg) mice that, due to hypoxia-independent erythropoietin (Epo) overexpression, reached hematocrit values of 0.8 to 0.9 without alteration of blood pressure, heart rate, or cardiac out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
138
0
6

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 114 publications
(162 citation statements)
references
References 52 publications
18
138
0
6
Order By: Relevance
“…Preparation of splenocytes -Mice were sacrificed, and their spleens were incubated with 1 mg/ml fresh collagenase D (Sigma) in RPMI for 30 min at 37 o C. Note that the tg6 spleen was enlarged (Vogel et al, 2003). The spleens were then immersed and forced through 200-m pore-size wire mesh, using the plunger from a 5 ml syringe to obtain a 7 single cell suspension.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Preparation of splenocytes -Mice were sacrificed, and their spleens were incubated with 1 mg/ml fresh collagenase D (Sigma) in RPMI for 30 min at 37 o C. Note that the tg6 spleen was enlarged (Vogel et al, 2003). The spleens were then immersed and forced through 200-m pore-size wire mesh, using the plunger from a 5 ml syringe to obtain a 7 single cell suspension.…”
Section: Methodsmentioning
confidence: 99%
“…More recently we noted EPO effects also on the humoral immune response of antigen-injected mice in both EPO-treated mice and tg6 mice (Ruschitzka et al, 2000;Vogel et al, 2003) -transgenic mice over-expressing human EPO (HuEPO) (Katz et al, 2007). Whereas these findings strongly suggest that EPO is an immunomodulator, the cellular mediators and underlying mechanisms are not understood, especially since EPO-Rs were not detected on lymphocytes ((Prutchi-Sagiv et al, 2006) and unpublished data).…”
Section: Introductionmentioning
confidence: 97%
“…Excessive erythrocytosis compromises vascular homeostasis as a result of significantly increased hematocrit and decreased plasma levels (Neunteufl et al, 2001). We have previously shown that NOmediated vasodilatation and increased blood viscosity are two ways by which tg6 mice adapt to the extremely high hematocrit levels (Vogel et al, 2003). However elevated blood viscosity significantly reduces blood velocity causing a concomitant lowering of shear stress to levels that are probably detrimental in the long term.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its well known role in erythropoiesis however a diverse array of cells have now been identified that produce Epo and/or express the Epo receptor including endothelial cells, smooth muscle cells and cells of the central nervous system (Digicaylioglu et al, 1995;Masuda et al, 1994). In vitro Epo has been shown to regulate a variety of neural functions such as calcium flux (Korbel et al, 2004) neurotransmitter synthesis and cell survival (Velly et al, 2010;Vogel et al, 2003). Furthermore Epo has neurotrophic effects (Chen et al, 2007;Grimm et al, 2002;Junk et al, 2002), can induce an angiogenic phenotype in cultured endothelial cells, is a potent angiogenic factor in vivo (Ribatti et al, 2003) and enhances ventilation in hypoxic conditions (Soliz et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation